Design and modelling of ultrasonic tomography for two-component high-acoustic impedance mixture - Mohd Hafiz, Fazalul Rahiman; Ruzairi, Abdul Rahim; Zulkarnay, Zakaria (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com